Importance of Zinc Concentration in Seminal Fluid of Men Diagnosed with Infertility - Milostic-Srb, Andrea; Vcev, Aleksandar; Tandara, Marijan; Maric, Svjetlana; Kuic-Vadlja, Vesna; Srb, Nika; Holik, Dubravka (Acta clinica Croatica (Tisak), 2020)
The prevalence and importance of male infertility make it a serious worldwide medical and social problem. The aim of this study was to determine if there were any significant differences in zinc concentrations in seminal fuid in men diagnosed with infertility compared to control group, and if there were, to determine how it affected the number and percentage of sperm cells with normal motility and morphology. A case-control study was conducted in the Osijek-Bara nja County from January 2014 to June of 2015. The study included 276 subjects referred to biochemistry laboratory of the Osijek University Hospital Centre, 100 (36.2%) of them with low sperm count confrmed by spermiogram after 3 months. Semen samples were processed according to the World Health Organization criteria, and zinc concentrations were determined using spectrophotometry and direct colorimetry without deproteinization on a chemistry analyzer (Olympus AU 680, Beckman Coulter, Tokyo, Japan). Study results showed the men with low sperm count to be significantly older (Mann Whitney U test: p=0.013) and to have lower zinc levels ([chi square]-test: p<0.001). Further analysis included 100 (36.2%) patients with low sperm count. In the group of infertile men, those with low sperm count had higher zinc levels compared to men with azoospermia (Mann Whitney U test: p=0.036), suggesting a connection between lower zinc level in seminal fuid and male fertility. Zinc as a biological marker and an antioxidant affects sperm count, motility and morphology. Zinc supplemental therapy could improve seminal parameters in patients diagnosed with low sperm count. Dietary habits of the subjects difer regionally, and future research could make a solid foundation for complementary approach to treatment of male infertility. Key words: Croatia; Infertility, male; Zinc; Case-control studies; Oligospermia; Semen